2020
DOI: 10.1038/s41598-020-62205-6
|View full text |Cite
|
Sign up to set email alerts
|

Renal carcinoma CD105−/CD44− cells display stem-like properties in vitro and form aggressive tumors in vivo

Abstract: clear cell renal cell carcinoma (ccRcc) is the most common kidney cancer. prognosis for ccRcc is generally poor since it is largely resistant to chemo-and radiotherapy. Many studies suggested that cancer stem cells/tumor initiating cells (CSCs/TICs) are responsible for development of tumor, disease progression, aggressiveness, metastasis and drug resistance. However, tumorigenic potential of CSCs/ tics isolated from established Rcc cell lines-basic ccRcc research model-has never been investigated in vivo. CD10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 77 publications
1
16
0
Order By: Relevance
“…S4A-C). The well-known clear cell renal cell carcinoma (CCRCC) CSC markers (ALDH1A1, CD44, CXCR4, DCLK1, CD105, ITGB1, NT5E, PIK3R1, PROM1 and THY1) [20][21][22][23][24][25][26][27] were displayed in the featurePlot to verify the expression in the identified CDRCCCSC cluster ( Supplementary Fig S5A, B). It was found that ALDH1A1, DCLK1, ITGB1 and PIK3R1 were also expressed in the identified CDRCC CSC cluster.…”
Section: Identification and Characterization Of Csc Populationmentioning
confidence: 99%
“…S4A-C). The well-known clear cell renal cell carcinoma (CCRCC) CSC markers (ALDH1A1, CD44, CXCR4, DCLK1, CD105, ITGB1, NT5E, PIK3R1, PROM1 and THY1) [20][21][22][23][24][25][26][27] were displayed in the featurePlot to verify the expression in the identified CDRCCCSC cluster ( Supplementary Fig S5A, B). It was found that ALDH1A1, DCLK1, ITGB1 and PIK3R1 were also expressed in the identified CDRCC CSC cluster.…”
Section: Identification and Characterization Of Csc Populationmentioning
confidence: 99%
“…These findings are consistent with the biological features of stem cells such as that they secrete multiple cytokines and regulate diverse immune cells [ 8 , 9 ]. Some reports indicated renal stem cells express mesenchymal and embryonic stem cell markers, namely octamer-binding transcription factor 4 (Oct-4) and paired box gene 2 (PAX2) in mouse renal tubules [ 10 , 11 ]. Cluster of differentiation (CD)24 and CD133 can also be expressed in the embryonic kidney [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…20,30 However, a recent study that used the Caki-1 cells derived from skin metastasis of ccRCC indicated that CD44 -/ENGcells enriched CSCs. 31 In this study, CSCs had high tumorigenicity with distinctive angiogenic and metabolic characteristics in subcutaneous models. Therefore, we examined the tumorigenicity in several microenvironments, including in the kidney, and verified whether endoglin serves as a marker for CSC/CICs in ccRCC, using parental ccRCC cells OS-RC-2 and their derivatives.…”
Section: Discussionmentioning
confidence: 64%
“… 34 A previous study reported that ENG – /CD44 – renal cancer cells displayed a distinctive capability to induce angiogenesis. 31 The interference of endothelial signaling may have resulted in the failure in angiogenesis and the lower tumorigenic capability of ENG + cells in subcutaneous inoculation model compared with colony formation in vitro, in which angiogenesis is not needed.…”
Section: Discussionmentioning
confidence: 99%